Manual Vacuum Aspiration During Early Pregnancy Failure: A Comparison of Sublingual and Vaginal Misoprostol for Pain Management - Amber Batool, Saima Muhammad Ali, Iffat Irshad3, Riffat Iqbal (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: compare sublingual and vaginal misoprostol in terms of mean pain score during manual vacuum aspiration in cases of early pregnancy failure. Methodology: A total of 100 women with missed abortions, blighted ovaries, and 9 gm/dl haemoglobin were investigated at Wateem Medical and Dental College, Rawat, Rawalpindi. Complete medical history, physical, and obstetrical exam. Same doctor used ultrasound to determine pregnancy. Grouping of patients was done randomly (based on table of random numbers). Group (A)(n=50) was evaluated two hours after sublingual misoprostol. Group (B) (n=50) got 400 g misoprostol in their vaginal posterior fornix and were evaluated 4 hours later. Before surgery, all patients were given ibuprofen and antibiotics. Pre-measurements included blood pressure, heart rate, and temperature. Manual vacuum suction was aided by a 10ml paracervical lidocaine block. During surgery, the patient was given a VAS. All women received paracetamol after operations (two 500 mg pills). Results: Group-A and B patients' mean ages were 25.87+5.16 and 25.17+4.32 years, respectively. In Group-A, the mean gestational age was 7.17+2.54 weeks and in Group-B, 6.85+3.93. In Group-A, mean parity was 3.09+2.34 and in Group-B, 4.45+2.63. Comparing sublingual and vaginal misoprostol in terms of mean pain score during manual vacuum aspiration in early pregnancy failure demonstrates a significant difference (p 0.0001). Conclusion: We found that the average pain score during manual vacuum aspiration was much lower in cases of early pregnancy failure when misoprostol was administered vaginally as opposed to sublingually. Keywords: Early pregnancy failure, manual vacuum aspiration, misoprostol, sublingual and vaginal, efficacy